A comparison of two treatments for childhood apraxia of speech: methods and treatment protocol for a parallel group randomised control trial - Murray Elizabeth; McCabe Patricia; Ballard Kirrie J (BMC, 2012)
Abstract Background Childhood Apraxia of Speech is an impairment of speech motor planning that manifests as difficulty producing the sounds (articulation) and melody (prosody) of speech. These difficulties may persist through life and are detrimental to academic, social, and vocational development. A number of published single subject and case series studies of speech treatments are available. There are currently no randomised control trials or other well designed group trials available to guide clinical practice. Methods/Design A parallel group, fixed size randomised control trial will be conducted in Sydney, Australia to determine the efficacy of two treatments for Childhood Apraxia of Speech: 1) Rapid Syllable Transition Treatment and the 2) Nuffield Dyspraxia Programme - Third edition. Eligible children will be English speaking, aged 4-12 years with a diagnosis of suspected CAS, normal or adjusted hearing and vision, and no comprehension difficulties or other developmental diagnoses. At least 20 children will be randomised to receive one of the two treatments in parallel. Treatments will be delivered by trained and supervised speech pathology clinicians using operationalised manuals. Treatment will be administered in 1-hour sessions, 4 times per week for 3 weeks. The primary outcomes are speech sound and prosodic accuracy on a customised 292 item probe and the Diagnostic Evaluation of Articulation and Phonology inconsistency subtest administered prior to treatment and 1 week, 1 month and 4 months post-treatment. All post assessments will be completed by blinded assessors. Our hypotheses are: 1) treatment effects at 1 week post will be similar for both treatments, 2) maintenance of treatment effects at 1 and 4 months post will be greater for Rapid Syllable Transition Treatment than Nuffield Dyspraxia Programme treatment, and 3) generalisation of treatment effects to untrained related speech behaviours will be greater for Rapid Syllable Transition Treatment than Nuffield Dyspraxia Programme treatment. This protocol was approved by the Human Research Ethics Committee, University of Sydney (#12924). Discussion This will be the first randomised control trial to test treatment for CAS. It will be valuable for clinical decision-making and providing evidence-based services for children with CAS. Trial Registration Australian New Zealand Clinical Trials Registry: ACTRN12612000744853